The Influence Of Postpartum Gymnastic On Acceleration Of Uterial Involution And Decreasing Of Pain In Post Partum Patients In The Midwifery Room Lubuk Sikaping Hospital - Hidayati, Hidayati; Gusrawati, Rina (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
One of the factors that support mothers in the recovery process is one of which is early mobilization that can help the mother in increasing uterine contractions during the postpartum period. The data obtained in the midwifery room at the Lubuk Sikaping Hospital, the number of mothers who gave birth spontaneously amounted to 240 people. Data obtained from mothers who experienced postpartum problems as many as 60 people. The puerperal problems were partly due to poor uterine contractions, post-heating infections, and postpartum hemorrhage. The purpose of this study was to see the influence of postpartum gymnastics on the acceleration of uterine involution and decrease of pain on the postpartum patient in midwifery room of LubukSikaping Hospital This research method used Quasi EksperimenResert method with One group pretest-posttest design approach design, then data is processed by using paired test. The sample in this study were 20 respondents. The average difference between before and after postnatal gymnastics is 0.600, with SD 0,516, P value 0,015 means that there is an influence of postpartum gymnastics on the acceleration of uterine involution on a postpartum patient in midwifery room of LubukSikaping Hospital. Average of pain difference before and After doing postpartum gymnastics is 0,700, with SD 0,823, got P-value 0,025 mean the existence of the influence of gymnastics to decrease of pain to the postpartum patient in midwifery room Lubuk Sikaping Hospital. The suggestion in this research is the result of this research can be the source of information Can be used as a guide for health workers on research that will be done about postpartum gymnastics and can be used as a source of guidance for personnel in midwifery room. For further research to examine the factors affecting the decrease in uterine involution.